If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + -1(z + -8) = 0 Reorder the terms: 4z + -1(-8 + z) = 0 4z + (-8 * -1 + z * -1) = 0 4z + (8 + -1z) = 0 Reorder the terms: 8 + 4z + -1z = 0 Combine like terms: 4z + -1z = 3z 8 + 3z = 0 Solving 8 + 3z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 3z = 0 + -8 3z = 0 + -8 Combine like terms: 0 + -8 = -8 3z = -8 Divide each side by '3'. z = -2.666666667 Simplifying z = -2.666666667
| 4x^2+5+3x-2+x^2+8x= | | 8(8x+2)=208 | | 1/2*4/3*3.14*9 | | -2-2m=-20 | | 4m-12=6m+6 | | f(x)=(9X)cos(x) | | 5z+12=4z+5 | | (x^2-2)/2=7 | | 7(-3+6K)= | | 6+(-n)-7=-2 | | 3c-5c=9+4c | | 4x+5=1x+2 | | x/8-(-2)=-3 | | 61.2=6(m+3.6) | | 4w-6=3(w+1) | | 12x+2x=10x+20 | | (3x-2)-x=10 | | 6(y-1/3)=-1.2(2y-10) | | 12y-21/4= | | -x+6y=16 | | 20cosX=-31.3229 | | 8d+4=2d | | 2x+41=83 | | 5x^3+36x+7=0 | | -12y-6x=3 | | x(14x+31)+15=0 | | -7a-2b+7+2b+5a= | | 39,41=120,84 | | (8x-3)-(7x-4)+(-5x+6)= | | 4x^3+12x^2-72x-160=0 | | 7x-28y=35 | | 7x(6x+1)=511 |